PKM KT Harapan Maju Desa Kiram Kabupaten Banjar - susilawati susilawati; Daniel Itta; Normela Rachmawati; Elda Nastitie Hidayah; Yusanto Nugroho (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Abstract In 2020, with the aim of helping farming communities, the manager of the Forest Area KHDTK with a Special Purpose (KHDTK) ULM provided assistance with 5 kelulut honey sticks for the Harapan Maju Farmers Group (KT) in Kiram Village. The initial purpose of this honey kelulut stup assistance was to empower farmers in Kiram Village who were affected by Covid 19 so that it was hoped that farmers who were members of KT Harapan Maju would have additional income apart from farming and farming. KT Harapan Maju in maintaining the aid of kelulut honey stup has several problems, namely (1) not being able to move and multiply the bee colony so that little honey is produced (2) The honey harvesting process carried out by KT Harapan Maju uses a manual suction device so it is less effective (3) Limited knowledge about honey packaging so that the resulting honey is marketable. To overcome the problems faced by the Harapan Maju farmer group in cultivating kelulut honey, the Service Team will (1) provide training on how to move bee colonies / break up bee colonies (3) improve the quality of harvesting equipment (4) Good honey packaging training so that it meets standards. The goal achieved in this service program is to provide knowledge for partners about professional honey bee cultivation techniques so that they can increase partners' income and ultimately reduce community activities in forest areas. Keywords: Forest, KHDTK, kelulut  AbstrakTahun 2020 lalu dengan tujuan membantu masyarakat petani, pengelola KHDTK Kawasan Hutan dengan Tujuan Khusus (KHDTK) ULM memberikan bantuan 5 buah stup madu kelulut untuk Kelompok Tani (KT) Harapan Maju Desa Kiram.  Tujuan awal bantuan stup madu kelulut ini adalah untuk memberdayakan petani di Desa Kiram yang terdampak Covid 19 sehingga diharapkan petani yang tergabung dalam KT Harapan Maju memiliki tambahan penghasilan selain bertani dan berladang. KT Harapan Maju dalam memelihara bantuan stup madu kelulut memiliki beberapa permasalahan yaitu (1) belum mampu memindahkan dan memperbanyak koloni lebah sehingga madu yang dihasilkan sedikit (2) Proses pemanenan madu yang dilakukan oleh KT Harapan Maju menggunakan alat sedot manual sehingga kurang efektif (3) Terbatasnya pengetahuan tentang pengemasan madu sehingga madu yang dihasilkan layak dipasarkan. Untuk mengatasi permasalahan yang dihadapi Kelompok tani Harapan Maju dalam budidaya madu kelulut maka Tim Pengabdi akan melakukan (1) memberikan pelatihan cara pemindahan koloni lebah/memecah koloni lebah (3) peningkatan kualitas alat panen (4) Pelatihan pengemasan madu yang baik sehingga memenuhi standar. Tujuan kegiatan Program Dosen Wajib Mengabdi (PDWA) ini yaitu membekali mitra dengan pengetahuan teknik perlebahan yang professional sehingga dapat meningkatkan pendapatan mitranya dan pada akhirnya mengurangi aktivitas masyarakat di kawasan hutan. Kata Kunci : Hutan, KHDTK, kelulut